Age period cohort analysis of chewing ability in Korea from 2007 to 2018 - Nam-Hee Kim (Nature Portfolio, 2021)
Abstract There have been marked improvements in oral health in Korea during the past 10 years, including chewing ability. We sought to disentangle age, period, and cohort effects in chewing ability between 2007 and 2018. We analyzed data from the Korea National Health and Nutrition Examination Survey. The main variable was chewing difficulty, which was assessed among participants aged 20 years and older. APC analysis revealed three trends in chewing difficulty: (1) there was an increase in chewing difficulty starting at around 60 years of age (age effect), (2) there was a steady decrease in chewing difficulty during the observation period (period effect), and (3) chewing ability improved with each successive generation born after 1951 (cohort effect). Regarding recent improvements in chewing ability, cohort effects were somewhat more important than period effects.